PENGUJIAN POMPA SENTRIFUGAL UNTUK MENGETAHUI PERUBAHAN KECEPATAN, DEBIT DAN KERUGIAN PADA DIAMETER PIPA 3/4 " UNTUK BERBAGAI VARIASI BUKAAN KATUB - RM. Bagus Irawan; Suratman - (JURNAL LITBANG, 2004)
In Planning to make a pump, pump characteric should be well - chosen because it determines its performance. In the research, a centrifugal pump experiment is aimed at knowing its characteristic. Based on the pump experiment, it shows that water stream speed, water - quantity and water loss are really influenced by rpm motor variation and valve tub variation on the installation.Key words: sentrifugal pump, charateristic